PENINGKATAN KETERAMPILAN MENULIS NARASI MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS IV SDN 15 ULU GADUT KECAMATAN PAUH KOTA PADANG: Penelitian Tindakan Kelas - Sari, Karmila; Muhammadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low level of narrative writing skills because teachers have not fully used innovative learning models. This research aims to describe how to improve narrative writing skills using the Problem Based Learning (PBL) model in class IV of SDN 15 Ulu Gadut, Pauh District, Padang City. This type of research is classroom action research, using qualitative and quantitative approaches. Implemented in two cycles, namely cycle I consisting of two meetings and cycle II consisting of one meeting. The subjects of this research were class teachers and students in class IV of SDN 15 Ulu Gadut, Pauh District, Padang City, with a total of 25 students consisting of 13 boys and 12 girls.The results of the research showed that there was an increase: a) the teaching module in cycle I obtained an average of 89.58 with a good predicate, an increase in cycle II obtained an average of 95.83 with a very good predicate; b) teacher activity in cycle I obtained an average of 83.92 with a good predicate, increasing in cycle II to an average of 92.85 with a very good predicate; c) student activity in cycle I obtained an average of 83.92 with a good predicate, increasing in cycle II to an average of 92.85 with a very good predicate; d) the results of improving narrative writing skills in cycle I obtained an average of 68.4 with a poor predicate, increasing in cycle II obtained an average of 88.8 with a good predicate. From the research results, it can be concluded that the Problem Based Leaning (PBL) model can improve narrative writing skills in class IV of SDN 15 Ulu Gadut, Pauh District, Padang City.